Проблеми керованості для рівняння струни - Фардигола, Л.В.; Халіна, К.С. (Український математичний журнал, 2007)
Получены необходимые и достаточные условия 0- и ε-управляемости для уравнения струны, управляемого краевыми условиями. Управления, решающие эти задачи, найдены в явном виде. Более того, с помощью тригонометрической проблемы моментов Маркова построены релейные управления, решающие задачу ε-управляемости. Necessary and sufficient conditions of the null-controllability and approximate null-controllability are obtained for the string equation controlled by boundary conditions. Controls solving these problems are found explicitly. Moreover, bang-bang controls solving the approximate null-controllability problem are constructed with the use of the Markov trigonometric moment problem.